2022
DOI: 10.1186/s13690-022-00815-4
|View full text |Cite
|
Sign up to set email alerts
|

Don’t change who we are but give us a chance: confronting the potential of community health worker certification for workforce recognition and exclusion

Abstract: Background For community health workers (CHWs) and promotores de salud (CHWs who primarily serve Latinx communities and are grounded in a social, rather than a clinical model of care), the process of certification highlights the tension between developing a certified workforce with formal requirements (i.e., certified CHWs) and valuing CHWs, without formal requirements, based on their roles, knowledge, and being part of the communities where they live and work (i.e., non-certified CHWs). Califo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…This would also allow CHWs to seek standardized wages and employers to develop insurance reimbursement infrastructure. This is further supported by other CHW assessments, including an assessment in California, where CHWs identified that certification may provide enhanced professional recognition, upward mobility, and higher compensation (Anabui et al, 2021;Ibe et al, 2020;Kissinger et al, 2022).…”
Section: Being In Favor Of Chw Certification Being Against Chw Certif...mentioning
confidence: 77%
See 3 more Smart Citations
“…This would also allow CHWs to seek standardized wages and employers to develop insurance reimbursement infrastructure. This is further supported by other CHW assessments, including an assessment in California, where CHWs identified that certification may provide enhanced professional recognition, upward mobility, and higher compensation (Anabui et al, 2021;Ibe et al, 2020;Kissinger et al, 2022).…”
Section: Being In Favor Of Chw Certification Being Against Chw Certif...mentioning
confidence: 77%
“…Other reasons include the loss of CHW identity and job‐specific training requirements. This has been substantiated in the literature, where there is concern that certification will prevent CHWs from obtaining employment or accessing minority populations (CDC, 2019; Clary, 2015; Ibe et al., 2020; Kissinger et al., 2022).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Lack of reimbursement models for SW is also a problem in our current healthcare financing. Further, we need to be familiar with the ongoing dialogue in the CHW field regarding certification and whether it will threaten CHW identity by removing them from the community through professionalisation or exclude some CHWs due to eligibility requirements (Kissinger et al, 2022). As the field of social work has had to grapple with similar dilemmas in the fee-for-service healthcare system, it will be important to continue advocating for collaboration and recognise that several models of collaboration may emerge due to differences in community settings or policy contexts.…”
Section: Razon Et Al (2019)mentioning
confidence: 99%